Self-repairing insulating composite material and preparation method thereof
By constructing self-healing insulating composite materials, the insulation performance problems of traditional insulating materials in lightweight and high-temperature environments are solved, the coordinated optimization of self-healing and electric field regulation is achieved, and the insulation performance and reliability of application scenarios such as new energy vehicle motors and high-voltage DC cables are improved.
Patent Information
- Application Number
- CN202511310456.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-09-15
AI Technical Summary
Traditional polymer insulation materials have difficulty balancing lightweight and high insulation performance in miniaturized and high-temperature environments. They are also prone to corrosion and damage, requiring regular maintenance, which affects equipment reliability.
A self-healing insulating composite material structure is adopted, including hollow silica microspheres as the insulating core, polyaniline nanoparticles deposited on the surface and polyethylene glycol-modified epoxy resin and dicyandiamide self-healing system encapsulated inside, to construct a self-healing core-insulating core-dielectric shell ternary synergistic structure.
The material achieves lightweight, high insulation and toughness, while also having self-repair capabilities, improving breakdown field strength and flexibility, adapting to wide temperature ranges, and improving equipment reliability.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of insulating materials, in particular to a self-repairing insulating composite material and a preparation method thereof. BACKGROUND
[0002] With the development of electronic and electrical equipment towards miniaturization, high power density and high temperature environment application, the performance requirements of the corresponding insulating materials are becoming more and more stringent. Traditional polymers (such as epoxy resin, polyimide, silicone rubber, etc.) need to be broken through in core indicators such as higher insulating strength and lightweight.
[0003] However, in the existing material system, in order to reduce the density of the material, a porous structure or a low-density filler needs to be introduced, but the increase of porosity easily leads to local electric field distortion, thereby reducing the insulating strength, and there is a problem of inversion of the relationship between material lightweight and insulating performance.
[0004] In addition, the intrinsic breakdown field strength of traditional polymers is limited, and if the performance is to be improved, the coating thickness needs to be increased, which is contrary to the development trend of equipment miniaturization; at the same time, due to the particularity of the application scene (hot and humid scene), the existing materials are prone to corrosion damage and other situations during use, which adversely affects the insulating performance of the materials, and therefore the materials need to be regularly inspected and maintained, and the damaged parts need to be replaced and repaired, which is time-consuming and laborious. SUMMARY
[0005] The purpose of the present application is to provide a self-repairing insulating composite material and a preparation method thereof, which can improve the insulating performance of the material while ensuring the lightweight of the material, and also has the function of self-repairing, providing a breakthrough insulating material solution for application scenarios such as new energy automobile motors and high-voltage direct current cables, and promoting the development of electronic and electrical equipment towards higher efficiency and reliability.
[0006] The technical solution of the present application is as follows: On the one hand, the present application provides a self-repairing insulating composite material, the structure of which comprises a self-repairing core system, an insulating core and a dielectric shell arranged from inside to outside in sequence. The insulating core is a hollow silica microsphere, the self-repairing core system comprises polyethylene glycol modified epoxy resin and dicyandiamide, and the dielectric shell is composed of polyaniline nanoparticles. The hollow cavity of the hollow silica microsphere is encapsulated with the self-repairing core system, and the surface of the hollow silica microsphere is deposited with the polyaniline nanoparticles to form the dielectric shell.
[0007] Further, in some embodiments of the present application, the particle size of the insulating core is 70-90 nm, the wall thickness is 15-25 nm, and the wall layer is composed of silica particles with a particle size of 5-10 nm.
[0008] Further, in some embodiments of the present application, the dielectric shell is composed of polyaniline nanoparticles with a particle size of 1-3 nm, and the distribution area of the polyaniline nanoparticles accounts for 20-25% of the surface area of the hollow silica microspheres.
[0009] In another aspect, the embodiments of the present application also provide a preparation method of the self-repairing insulation composite material, which comprises the following steps: S1 Preparation of polyethylene glycol modified epoxy resin: taking epoxy resin and polyethylene glycol, and reacting under the action of a catalyst to prepare polyethylene glycol modified epoxy resin; S2 Preparation of silica microspheres: taking the prepared polyethylene glycol modified epoxy resin and finely divided dicyandiamide, and dissolving them in toluene as an oil phase; taking a solution containing hydrochloric acid and sodium dodecyl sulfonate as an aqueous phase; forming an O / W emulsion system through high-speed shearing emulsification, and adding tetraethyl orthosilicate dropwise into the O / W emulsion system to react, so that the tetraethyl orthosilicate is hydrolyzed and condensed to form a silica shell layer at the oil-water interface; centrifuging and washing the obtained product with ethanol, and drying to obtain silica microspheres encapsulating the polyethylene glycol modified epoxy resin; S3 Polyaniline deposition: taking the prepared silica microspheres, adding an aqueous hydrochloric acid solution, and dispersing by ultrasonic; adding aniline and stirring to obtain a mixture; taking ammonium persulfate and dissolving it in an aqueous hydrochloric acid solution by ultrasonic to obtain an ammonium persulfate-aqueous hydrochloric acid solution; adding the ammonium persulfate-aqueous hydrochloric acid solution dropwise into the mixture to react, obtaining a reaction product, and filtering, washing, and drying to obtain a finished product.
[0010] Further, in some embodiments of the present application, in the preparation step of the polyethylene glycol modified epoxy resin, the molar ratio of the used epoxy resin and polyethylene glycol is 1:0.8-1:1.5, and the used catalyst is triphenylphosphine, and the catalyst dosage is 0.1% of the total mass of the epoxy resin and polyethylene glycol.
[0011] Further, in some embodiments of the present application, in the preparation step of the silica microspheres, fumed silica is additionally added in the process of forming the O / W emulsion system through high-speed shearing emulsification to prevent sedimentation.
[0012] Further, in some embodiments of the present application, in the preparation step of the silica microspheres, the prepared polyethylene glycol modified epoxy resin and 5-10 wt% finely divided dicyandiamide are co-dissolved in toluene as an oil phase; a solution containing 0.1 M hydrochloric acid and 0.5 wt% sodium dodecyl sulfonate is used as an aqueous phase, and 1 wt% fumed silica is additionally added to form the O / W emulsion system through high-speed shearing emulsification.
[0013] Further, in some embodiments of the present application, in the step of preparing the silica microspheres, the diameter of the emulsion droplets in the O / W emulsion system is 200-500 nm.
[0014] Further, in some embodiments of the present application, in the step of preparing the silica microspheres, the tetraethyl orthosilicate is added dropwise into the O / W emulsion system at room temperature.
[0015] Further, in some embodiments of the present application, in the step of depositing the polyaniline, the ammonium persulfate-hydrochloric acid aqueous solution is added dropwise into the mixture at an ice bath.
[0016] Further, in some embodiments of the present application, in the step of depositing the polyaniline, the weight ratio of aniline to silica microspheres is 0.15-0.25:1.
[0017] Compared with the prior art, the embodiments of the present application have at least the following advantages or benefits: For the above-mentioned aspects, the embodiments of the present application provide a self-repairing insulation composite material and a preparation method thereof, which constructs a ternary synergistic structure of "self-repairing core-insulation core-dielectric shell", and realizes the synergistic improvement of lightweight, high insulation, toughness and self-repairing. Specifically, it takes hollow silica microspheres (HSMS) as the insulation core, deposits polyaniline nanoparticles (PANI) on the surface, and encapsulates a polyethylene glycol (PEG) modified epoxy resin and a dicyandiamide curing agent self-repairing system in the interior.
[0018] Among them, the hollow silica microspheres can effectively suppress the generation of leakage current and meet the lightweight demand due to their excellent insulation performance and low density characteristics; the resistivity of the surface polyaniline nanoparticles can be accurately controlled in the range of 10 6 -10¹ 0 Ω·cm, and as efficient charge traps, it significantly delays the migration of carriers; the PEG modified epoxy resin acts as a soft template and a self-repairing component, and its PEG segment can guide the directional growth of the silica shell layer and also act as a plasticizing medium to trigger the release of the curing agent at low temperature, and can autonomously repair microcracks when mechanically damaged, realizing the self-repairing function. Its self-repairing mechanism is easy to trigger, and can greatly improve the practicability of the material.
[0019] In addition, the hollow silica insulating core and the nanoscale polyaniline dielectric shell jointly build a "charge trap-insulating barrier" synergistic network, which greatly improves the breakdown field strength by absorbing local charges and dispersing electric field intensity, and only a small amount of addition is needed in the composite material to significantly improve the insulation performance, thereby greatly reducing the density of the composite material. The PEG segment acts as a plasticizer to significantly improve the overall elongation at break of the material; the flexible long molecular chain of PEG forms a "molecular pulley" effect with SiO2, PANI and the like, so that the composite material maintains excellent flexibility in a wide temperature range of-40℃ to 120℃; the PEG segment can enhance the interfacial compatibility, so that the performance retention rate of the composite material after damp-heat aging at 85℃ / 85% RH is still greater than 95%.
[0020] In summary, the application creatively builds a self-repairing system composed of PEG modified epoxy resin and dicyandiamide as encapsulating material, constructs hollow silica insulating core on its surface, and deposits polyaniline on the surface; realizes the synergistic optimization of "self-repairing-electric field regulation-interface stability", and provides a breakthrough solution for insulating materials for new energy automobile motor, high-voltage DC cable and other application scenarios, and promotes the development of electronic and electrical equipment to be more efficient and more reliable. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the embodiments of the application more clear, the technical scheme in the embodiments of the application will be clearly and completely described below. If the specific conditions are not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments used are not specified by the manufacturer, they are all conventional products that can be purchased on the market.
[0022] It should be noted that the terms "comprising", "containing" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed or inherent to such a process, method, article or equipment. Without more limitations, the elements defined by the statement "comprising" do not exclude the presence of other identical elements in the process, method, article or equipment including the elements.
[0023] It should be noted that the embodiments in the application and the features in the embodiments can be combined with each other without conflict.
[0024] The features and properties of the application will be further described below in combination with the embodiments.
[0025] Embodiment 1 The self-repairing insulation composite provided by the embodiment of the present application comprises, from inside to outside, a self-repairing core system, an insulation core, and a dielectric shell; the insulation core is a hollow silica microsphere; the self-repairing core system comprises polyethylene glycol modified epoxy resin and dicyandiamide; and the dielectric shell is composed of polyaniline nanoparticles. The hollow cavity in the hollow silica microsphere is encapsulated with the self-repairing core system; the surface of the hollow silica microsphere is deposited with the polyaniline nanoparticles to form the dielectric shell. The insulation core has a particle size of 70-90 nm and a wall thickness of 15-25 nm, and the wall layer is composed of silica particles with a particle size of 5-10 nm. The dielectric shell is composed of polyaniline nanoparticles with a particle size of 1-3 nm, and the distribution area of the polyaniline nanoparticles accounts for 20-25% of the surface area of the hollow silica microsphere.
[0026] The self-repairing insulation composite is prepared by the following method: S1 Preparation of polyethylene glycol modified epoxy resin: epoxy resin (E-51) and polyethylene glycol (PEG) are taken in a molar ratio of 1:1, and under the action of a catalyst (0.1 wt% triphenylphosphine), the mixture is reacted at 80°C for 6 h to prepare polyethylene glycol modified epoxy resin; S2 Preparation of silica microspheres: oil phase preparation: 30 g of polyethylene glycol modified epoxy resin and 2.5 g of micronized dicyandiamide are weighed in a beaker, and 100 mL of toluene is added. Stir in a 50-60°C water bath until completely dissolved and clear. Water phase preparation: in another beaker, 0.5 g of sodium dodecyl sulfate (SDS) is dissolved in 90 mL of deionized water, and then 10 mL of 0.1M hydrochloric acid solution is added, and stirred uniformly. Finally, 1 g of fumed silica is added, and a high-speed shearing emulsifier (such as 10000 rpm, 2 minutes) is used for pre-dispersion.
[0027] Continue high-speed shearing emulsification at a speed of 10000 rpm for 10 min to form an O / W emulsion system (droplets 200-500 nm), and add 40 mL of tetraethyl orthosilicate (TEOS) dropwise into the 200 mL O / W emulsion system, and react at room temperature for 12 h to make the tetraethyl orthosilicate hydrolyze and condense to form a silica shell layer at the oil-water interface; the obtained product is centrifuged and washed with ethanol for 3 times, and then dried in a constant temperature oven for 12 h to obtain silica microspheres encapsulating polyethylene glycol modified epoxy resin; S3 Polyaniline deposition: Take the prepared silica microspheres 2 g, add 100 ml 0.1M hydrochloric acid aqueous solution, ultrasonic 10 min, disperse uniformly, then add 0.3 g aniline, magnetically stir uniformly, get the mixture; Take another 0.37 g ammonium persulfate (APs) into 100 ml 0.1M hydrochloric acid aqueous solution, ultrasonic dissolve transparent, get ammonium persulfate-hydrochloric acid aqueous solution; Through the peristaltic pump control, add ammonium persulfate-hydrochloric acid (APs-HCl) aqueous solution into the mixture for 30 min, react for 5 h under ice bath condition, then stand for 2 h, get the reaction product, after suction filtration, deionized water and ethanol alternative washing, and 80°C vacuum oven drying for 24 h, get the powder, which is the product, surface deposition of polyaniline, internal encapsulation of PEG modified epoxy resin and dicyandiamide curing agent self-repairing system silica microspheres composite material, recorded as PANI-HSMS-E1.
[0028] Example 2 The present example provides a self-repairing insulation composite material, which is only different from example 1 in that: in the preparation method: in step S1, the molar ratio of epoxy resin (E-51) and polyethylene glycol (PEG) is 1:1.5; the prepared composite material is recorded as PANI-HSMS-E2.
[0029] Example 3 The present example provides a self-repairing insulation composite material, which is only different from example 1 in that: in the preparation method: in step S3, the weight ratio of aniline and silica microspheres meets 0.25:1, that is, take aniline 0.5 g, silica microspheres 2 g; the prepared composite material is recorded as PANI-HSMS-E3.
[0030] Comparative Example 1 The present comparative example provides an insulation material, which is solid silica microspheres, recorded as SS.
[0031] It is prepared by the following method: In a beaker, mix 10 milliliters (25-28%) ammonia water and 150 milliliters of anhydrous ethanol and 15 milliliters of deionized water to get solution A; Mix 5 milliliters of TEOS and 20 milliliters of anhydrous ethanol in a beaker to get solution B; Under high-speed magnetic stirring, quickly add solution B to solution A, after 3 min of reaction, reduce the stirring speed, seal the flask, and react at room temperature for 2 h. After centrifugation and washing with ethanol for 3 times, put the product into a constant temperature oven, dry at 130°C for 6 h, cool the product, and seal for use.
[0032] Comparative Example 2 This comparative example provides an insulating material, which is polyaniline deposited solid silica microspheres, denoted as PANI-SS.
[0033] It is prepared by the following method: Take 2 g of SS prepared in Comparative Example 1, add to 100 ml of 0.1M aqueous hydrochloric acid, ultrasonic for 10 min, uniformly dispersed, then add 0.3 g of aniline, open the magnetic stirring, stir evenly, get the mixture. Another 0.37 g of APs is taken and added to 100 ml of 0.1M aqueous hydrochloric acid, ultrasonic to dissolve transparent, get APs-HCl aqueous solution, control with peristaltic pump, add APs-HCl aqueous solution to the mixture dropwise for 30 min, after dropwise addition is completed, react for 5 h under ice bath condition, then stand for 2 h. Then by suction filtration, and washed with deionized water and ethanol alternately until the filtrate is colorless. The obtained dark green solid is dried in a vacuum oven at 80℃ for 24 h. The obtained powder is polyaniline deposited solid silica (PANI-SS).
[0034] Comparative Example 3 This comparative example provides an insulating material, which is hollow silica microspheres, denoted as HSMS.
[0035] It is prepared by the following method: Pour 20 g of styrene (St) into a high-pressure reaction kettle, add 300 g of ethanol / water (2:1), then add 0.8 g of azobisdimethylaminoformamide hydrochloride (AIBA) and 10 g of polyvinylpyrrolidone (PVP) dissolved in the solution, ultrasonic dispersion for 10 min; after heating for 10 h, centrifuge after cooling, wash the centrifuged product with water twice and ethanol twice; put the washed product into a constant temperature oven and dry for 12 h to obtain polystyrene (PS) microspheres, seal for later use. The obtained PS microspheres have a diameter of 80 nm. The diameter of the PS microspheres can be adjusted by adjusting the ratio of St, ethanol and water, and the amount of PVP and AIBA.
[0036] Take 6 g of PS microspheres (diameter 80 nm) and add to 1000 ml of ethanol / water (28 ml) solution, ultrasonic dispersion for 10 min; under magnetic stirring, add 45 ml of tetraethyl orthosilicate (TEOS) and 20 ml of ammonia water respectively, constant temperature reaction for 5 h, then centrifuge the product, wash with ethanol for 3 times, and dry in a constant temperature oven for 12 h to obtain styrene-silica microspheres; The styrene-silica microspheres are calcined in a muffle furnace, heated to 550℃ at a rate of 5℃ / min, kept for 5 h, cooled and discharged to obtain hollow silica microspheres (HSMS) with a wall thickness of 15 nm, seal for later use.
[0037] Comparative Example 4 The comparative example provides an insulating material, which is polyaniline deposited hollow silica microspheres, denoted as PANI-HSMS.
[0038] It is prepared by the following method: Take 2 g of HSMS prepared in Comparative Example 3, add it to 100 ml of 0.1M hydrochloric acid aqueous solution, ultrasonic for 10 min, uniformly dispersed, then add 0.3 g of aniline, then start magnetic stirring, stir uniformly, to obtain a mixture. Take another 0.37 g of APs and add it to 100 ml of 0.1M hydrochloric acid aqueous solution, ultrasonic to dissolve transparently, to obtain an APs-HCl aqueous solution, control with a peristaltic pump, and drop the APS-HCl aqueous solution into the mixture for 30 min. After the drop is completed, react for 5 h under ice bath conditions, then stand for 2 h. Then, through suction filtration, and wash with deionized water and ethanol alternately until the filtrate is colorless. The obtained dark green solid is dried in a vacuum oven at 80°C for 24 h. The obtained powder is polyaniline deposited hollow silica microspheres (PANI-HSMS).
[0039] Comparative Example 5 The comparative example provides a self-repairing insulating composite material, which is different from Example 1 only in that in the preparation method: in step S3, the weight ratio of aniline and silica microspheres satisfies 0.6:1, i.e. take 1.2 g of aniline and 2 g of silica microspheres; the prepared composite material is denoted as PANI-HSMS-E4.
[0040] Comparative Example 6 The comparative example provides an insulating material, which is a cycloaliphatic epoxy material, as a blank example.
[0041] It is prepared by the following method: Mix 100 g of 3,4-epoxycyclohexyl carboxylic acid-3,4-epoxycyclohexyl methyl ester cycloaliphatic epoxy resin, 90 g of methyl tetrahydrophthalic anhydride curing agent, 1 g of 2,4,6-tris(dimethylaminomethyl) phenol accelerator and 220 g of aluminum hydroxide filler together, and fully stir them by a stirring disperser. Then, introduce the stirred mixture into a mold, and then put it into a vacuum oven at 50-60°C, and perform vacuum extraction at an atmospheric pressure of-0.1 MPa for 30 min, to ensure that the residual air in the mixture is completely extracted.
[0042] After vacuum extraction, put the mold into a constant temperature oven at 120°C for 10 h for complete curing, and finally cool and demold to obtain the cycloaliphatic epoxy material.
[0043] Comparative Example 7 The comparative example provides a self-repairing material, which is prepared by the following method: First, an oil phase (dissolved in 100 mL of toluene) containing 30 g of polyethylene glycol-modified epoxy resin and 2.5 g of finely divided dicyandiamide was stirred to clarify in a 50-60°C water bath. Subsequently, 0.5 g of sodium dodecyl sulfate (SDS) was dissolved in 90 mL of deionized water, and 10 mL of a 0.1M hydrochloric acid solution was added as an aqueous phase. The oil phase was slowly added to the aqueous phase under high-speed shearing (10000-15000 rpm) to form an oil / water emulsion (droplet size 1-10 μm) for 5-10 minutes. After the emulsion was transferred to a three-necked flask, 1.8 g of a water-soluble chain extender ethylenediamine (dissolved in 10-20 mL of water) was added to the system. After warming to 50-60°C, 5.0 g of diisocyanate (TDI, dissolved in 10-20 mL of toluene) was slowly added (30-60 minutes for dropwise addition) to the emulsion through a constant-pressure dropping funnel under mechanical stirring at 300-500 rpm. After the addition was completed, the reaction was continued at 50-60°C for 4-6 hours to allow the isocyanate and amine chain extender to polymerize sufficiently at the oil-water interface to form a dense polyurethane wall layer. After the reaction was completed, centrifugal separation (4000 rpm, 10 min) was performed, and washing was performed three times alternately with anhydrous ethanol and deionized water, and finally vacuum drying was performed at 40-50°C for 12-24 hours to obtain a polyurethane-coated microcapsule product, denoted as PU-E.
[0044] Test Examples The alicyclic epoxy material provided in Comparative Example 6 was used as a matrix, and the insulating materials provided in Examples 1-3 and Comparative Examples 1-5 and the self-repairing material provided in Comparative Example 7 were added respectively to prepare composite insulating materials, and the obtained composite insulating materials were respectively subjected to performance testing.
[0045] The raw material ratios of the composite insulating materials of each group are shown in Table 1: Table 1 Raw material ratios of each test example
[0046] The test items and test methods are as follows: Impact resistance: The impact strength was tested according to ISO 179-1 / 1eU, and the sample was placed horizontally on two support seats to ensure that the long axis direction of the sample was perpendicular to the support line. The impact surface of the sample should face the pendulum. The support span was adjusted according to the thickness of the sample. For example: for a 4 mm thick sample, the span was 62 mm (the ISO 179 specified span was 16 times the thickness, i.e. 4 x 16 = 64 mm, and the actual span was usually simplified to 62 mm). The pendulum was raised to the standard starting height (the energy scale was reset to zero). The pendulum was released to freely fall and impact the center of the sample. The residual energy (or energy loss value) of the pendulum after breaking the sample was recorded.
[0047] Volume resistivity: The volume resistivity of the sample was measured by a high resistance meter (6517A) produced by the American Keithley Company, a three-electrode method was used for testing, the sample box was Model 8009, the test voltage was 500 V, the test temperature was 20 DEG C, and the sample thickness was 1 mm. For high insulation materials, at the initial stage of applying voltage, the current is mainly the polarization current, and with the extension of time, the polarization is completed, at this time the current is mainly the current caused by impurity ions. In order to reduce the polarization current and the interference of environmental factors, when the resistivity test is carried out, the time required for the current to reach stability needs to be determined first. The sample was applied with a voltage of 500 V for a period of time, and the current reached stability after 50 s, and 150 s was used as the stable time in the subsequent experiment. Each sample was tested for 5 times, and the average value was taken as the volume resistivity of the sample.
[0048] Dielectric strength: The dielectric constant and dielectric loss of the composite material were measured by a precision impedance analyzer (4294A) produced by the American Agilent, the test temperature was 20 DEG C, the test voltage was 0.5 V, the test frequency was 40-106 Hz, and the sample thickness was 1 mm.
[0049] Self-repairing performance test: The epoxy resin standard sample containing composite filler (size 100x10x2 mm) was prepared, a standard crack (width 100±5 μm, depth 1 mm) was prepared by using a diamond blade, the damaged sample was placed in an 80 DEG C oven for 2 h, and then naturally cooled to room temperature and placed for 24 h. The dielectric constant and dielectric loss of the composite material before and after damage were measured by a precision impedance analyzer (4294A) produced by the American Agilent.
[0050] The test results are shown in Tables 2 and 3.
[0051] Table 2 Mechanical and electrical properties of each experimental example
[0052] Table 3 Self-repairing performance of each experimental example
[0053] It can be seen from the results that the PANI-HSMS-E material prepared by the embodiment of the application can effectively improve the mechanical and insulating properties of the insulating material when applied to the composite insulating material, and at the same time, the material is endowed with self-repairing ability, and has excellent performance.
[0054] In conclusion, the embodiment of the present application provides a self-repairing insulation composite material and a preparation method thereof, which not only solves the contradiction between light weight and high reliability of traditional insulation materials, but also realizes the synergistic optimization of "self-repairing-electric field regulation-interface stability" through multi-functional integration, thereby providing a breakthrough insulation material solution for new energy automobile motor, high-voltage direct current cable and other application scenarios, and promoting the development of electronic and electrical equipment to be more efficient and more reliable.
[0055] The above-described embodiments are part of the embodiments of the present application, rather than all the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the claimed application, but only represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without creative labor fall within the scope of protection of the present application.
Claims
1. A self-repairing insulating composite material, characterized in that: Its structure includes a self-repairing core system, an insulating core and a dielectric shell arranged in sequence from the inside to the outside; The insulating core is a hollow silica microsphere, the self-repairing core system includes polyethylene glycol-modified epoxy resin and dicyandiamide, and the dielectric shell is composed of polyaniline nanoparticles; The self-repairing core system is encapsulated in the inner cavity of the hollow silica microsphere; the polyaniline nanoparticles are deposited on the surface of the hollow silica microsphere to form the dielectric shell.
2. The self-repairing insulating composite material according to claim 1, characterized in that: The insulating core particle size is 70-90 nm, the wall thickness is 15-25 nm, and the wall layer is composed of silicon dioxide particles with a particle size of 5-10 nm.
3. The self-repairing insulating composite material according to claim 1, characterized in that: The dielectric shell is composed of polyaniline nanoparticles with a particle size of 1 to 3 nm, and the distribution area of the polyaniline nanoparticles accounts for 20 to 25% of the surface area of the hollow silica microspheres.
4. A method for preparing the self-repairing insulating composite material according to any one of claims 1 to 3, characterized in that: The steps include: S1 Preparation of polyethylene glycol-modified epoxy resin: epoxy resin and polyethylene glycol are reacted in the presence of a catalyst to prepare polyethylene glycol-modified epoxy resin; Preparation of S2 silica microspheres: The prepared polyethylene glycol-modified epoxy resin and micronized dicyandiamide were dissolved in toluene as the oil phase; a solution containing hydrochloric acid and sodium dodecyl sulfate was used as the aqueous phase; An O / W emulsion system is formed by high-speed shear emulsification, and ethyl orthosilicate is added dropwise to the O / W emulsion system to react, so that the ethyl orthosilicate is hydrolyzed and condensed at the oil-water interface to form a silica shell layer; the obtained product is centrifuged and washed with ethanol, and dried to obtain silica microspheres encapsulated with polyethylene glycol-modified epoxy resin; S3 polyaniline deposition: the prepared silica microspheres are added to a hydrochloric acid aqueous solution and ultrasonically dispersed, and then aniline is added and stirred to obtain a mixture; ammonium persulfate is also added to the hydrochloric acid aqueous solution and ultrasonically dissolved to obtain an ammonium persulfate-hydrochloric acid aqueous solution; the ammonium persulfate-hydrochloric acid aqueous solution is dropwise added to the mixture to react to obtain a reaction product, which is filtered, washed, and dried to obtain a finished product.
5. The method for preparing the self-repairing insulating composite material according to claim 4, characterized in that: In step S1, the molar ratio of the epoxy resin to the polyethylene glycol is 1:0.8 to 1:1.
5.
6. The method for preparing the self-repairing insulating composite material according to claim 4, characterized in that: In step S2, during the process of forming the O / W emulsion system by high-speed shear emulsification, fumed silica is further added to prevent sedimentation.
7. The method for preparing the self-repairing insulating composite material according to claim 6, characterized in that: In step S2, the prepared polyethylene glycol-modified epoxy resin and 5-10 wt% of micronized dicyandiamide are co-dissolved in toluene as an oil phase; A solution containing 0.1 M hydrochloric acid and 0.5 wt% sodium dodecyl sulfate was used as the aqueous phase, and 1 wt% fumed silica was added to form an O / W emulsion system through high-speed shear emulsification.
8. The method for preparing the self-repairing insulating composite material according to claim 4, characterized in that: In step S2, in the formed O / W emulsion system, the diameter of the emulsion droplets is 200 to 500 nm.
9. The method for preparing the self-repairing insulating composite material according to claim 4, characterized in that: In step S2, ethyl orthosilicate is added dropwise to the O / W emulsion system at room temperature to carry out a reaction.
10. The method for preparing the self-repairing insulating composite material according to claim 4, characterized in that: In step S3, the weight ratio of the aniline to the silica microspheres satisfies 0.15-0.25:1.
Citation Information
Patent Citations
Hollow nano silica microsphere modified polyacrylate nuclear shell structure composite emulsion and thin film
CN101899128A
Preparation method of electromagnetic composite hollow microspheres
CN103157412A
Polymer-matrix composite material and preparation method thereof
CN104725778A
Composite shell microcapsule with self-repairing and anti-corrosion function and preparation method thereof
CN109535315A
Eco-friendly protection coating material and coating method using the same, and applied products
KR102669755B1